Komitmen Unicef dalam Menangani Masalah Pengungsi Anak Korban Perang Suriah di Turki - Restu Amelia; Shary Charlotte Henriette Pattipeilohy (Journal of International Relations Diponegoro, 2020)
Syrian civil war that occurred since 2011 has a devastating impact to country, society, and the international community. This war has caused many casualties and refugees which continues to increase every year. From the data collected by UNHCR, Syrian refugees have reached more than five million people and dominated by children. Until 2018, Turkey has become one of the largest host countries for the Syrian refugees. Unfortunately, the large number of refugees causing many problems. The purpose of this study explains the efforts made by the United Nations Children's Fund (UNICEF) in handling the problem of Syrian refugee children in Turkey from 2011 to 2018. This research is carried out by using descriptive analysisand qualitative methods. This research uses the concept of international organization and the concept of refugees. Data collection was performed using library research. This study showed that the efforts made by UNICEF inhandling the problem of Syrian refugee children include ensuring food and environmental security, health, and guaranteeing personal security which includes the right of access to education for children.